Thermal and Morphological Properties of Polypropylene/Styrene-Butadiene-Styrene Nanocomposites. Issue 15 (13th October 2018) - Mubarak, Y. A.; Abu-Halimeh, R.; Schubert, D.
ABSTRACT: Polypropylene/styrene-butadiene-styrene fumed silica nanocomposites were mixed in a twin screw Brabender Plasticorder, the weight percent of the SBS was varied at (0, 5, 10, 20, and 40), and the fumed silica content was varied at (0, 0.05, 0.1, 0.5, 1, and 2) wt%. The thermal and morphological properties of these nanocomposites were studied using a differential scanning calorimetry and a polarized light microscopy. It has been found that the addition of styrene-butadiene-styrene or fumed silica nanoparticles alone to polypropylene did not change the melting temperature while the existence of both elements changed the melting temperature of polypropylene slightly. Also, increasing the percentage of fumed silica nanoparticles leads to an increase in the crystallization temperature while styrene-butadiene-styrene increment has no effect. The melting peaks obtained by the differential scanning calorimetry revealed that increasing the styrene-butadiene-styrene content reduces the percentage crystallinity as a result of increasing the amorphous portion. The addition of styrene-butadiene-styrene to polypropylene has a very slight effect on the relative percentage crystallinity when calculations are performed based on the quantity of polypropylene within the composite. Although fumed silica nanoparticles aided and accelerating the nucleation step but it could not increase the percentage crystallinity of polypropylene beyond the percentage crystallinity of neat polypropylene. GRAPHICAL ABSTRACT: